Community Service- Disaster Covid-19 (PKM-BC19) In Alai Parak Kopi And Sweet Water Beach, Padang City, West Sumatera Province - Sayuti, Kesuma; Nagara Putra, Prima (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2021)
Community Service for the Covid-19 Disaster (PKM-BC) is an activity carried out by students accompanied by supervisors which aims to help the government to overcome the spread of the Covid-19 outbreak, in this service activity students act as providers of education to the community, regarding the symptoms of Covid-19 and cleanliness to prevent the transmission of Covid-19 and also help provide basic material assistance for people in need during this pandemic, so that people are expected to be more assisted and alert in responding to the spread of Covid-19. This activity was carried out in several areas in the city of Padang, especially in Alai Parak Kopi and the Air Manis Beach area, Padang City, West Sumatra Province. The work program carried out includes main activities, supporting and additional activities. The main activity of this service is the distribution of basic necessities, hand sanitizer and masks. As well as supporting activities from this service, in collaboration with Perumda PSM in the water sweet beach area, the work program is the enforcement of the Covid-19 protocol, spraying disinfectants and cleaning the sweet water beach. Supporting activities are making videos of making chlorophyll juice by utilizing local water spinach in the Alai Parak Kopi area.